N-acetylcysteine and ascorbic acid-2-phosphate incorporatedhydrogels as autologous stem cell delivery system for the treatment of diabetic wounds. - Meeser, Michelle (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2023.